Laparoscopic adrenalectomy for a giant adrenal myelolipoma: A case report. (January 2022) - Tinozzi, F.P.; Morone, G.; Calì, B.; Rebba, A.; Osman, N.; Albertario, S.; Abbiati, F.; Ruggiero, R.
Abstract: Case presentation: We describe a case of a patient who presented with a mildly symptomatic, giant myelolipoma which was excised by laparoscopic approach without complications. Introduction and importance: Adrenal myelolipoma (AML) is a rare tumour composed by fat and myeloid tissues. Usually it is asymptomatic, so the diagnosis is mostly incidental. It is generally located in the right adrenal gland, but it can also be found bilaterally. If its size exceeds 10 cm it is defined as a "giant myelolipoma"; in this case its treatment of choice would be adrenalectomy with an open surgical approach. Clinical discussion: Patient's signs and symptoms were mild pain in the right hypochondrium and a positive right Giordano's sign. The mass was detected by a contrast-enhanced CT scan. Once excised it measured 16 cm. Conclusion: Laparoscopic adrenalectomy for giant myelolipoma is a safe approach if performed by an expert surgeon, with low risk of bleeding and a better outcome for the patient. Highlights: Literature evidences are scarce regarding the surgical management of giant adrenal myelolipomas. Laparoscopic surgery is safe and feasible even for adrenal lesions larger than 10 cm. Clear resection margins can be obtained even for massive adrenal tumors.